لبنوك الإسلامية في سلطنة عُمان بين دعم و رقابة البنك المركزي - كامل عبد الله, أمال (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
Omani experience is considered the latestin the Arab world in the field of Islamic banks.the Omani legislatorallo wed this kind of banking activityin2012. This paper deals with an analytical study of the role of the Central Bank of Oman in support of Islamic banks through funding in accordance with its nature based on avoiding banking interests , also the paper includes an analysis of the supervisory role exercised by the Omani central bank to ensure good performance of Islamic banks and to avoid the negative effects of the risks of the banking business, such as liquidity risk and credit risk. This study explain the mechanism of cooperation between the Central Bank and Islamic banks and the tools of supervision exercised by the central bank to control Islamic banking in Oman, to provide an assessment to the role of the Central Bank in this area.